Reflecting on climate change education (CCE) initiatives for mitigation and adaptation in South Africa - Sibanda, Arorisoe; Manik, Sadhana (Environmental Education Research, 2022)
South Africa remains the largest emitter of carbon dioxide, a greenhouse gas, in Africa. As such despite the glowing government policy documents addressing climate change, efforts towards achieving the targets of the sustainable development goals (especially SDG 13) at grassroots level remain significant. We identified relevant published articles and grey literature on CCE. A thematic analysis of these publications focused on identifying the common CCE initiatives being actioned in SA. The major themes on CCE in respect of mitigation and adaption included: CCE initiatives promoted and articulated through the media, school community projects, the development of the school and higher education curricula for CCE, the development of associated teaching materials and guides. The findings revealed that despite the evidence of robust education initiatives for climate change mitigation and adaptation in published reports, there was greater emphasis on short term responses at the expense of long-term mitigation efforts.
Keywords: C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change education; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11488 Perceptions and Communication of Climate Change; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Discourses of climate change education: The case of geography textbooks for secondary and higher secondary education in South Africa and Norway - Trædal, Leif Tore; Eidsvik, Erlend; Manik, Sadhana (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2022)
The purpose of the article, which is a comparative study, is to explore climate change discourses in South African and Norwegian geography textbooks by addressing the following questions: What policy discourses of climate change can be identified in the textbooks? How is the climate change content of geography textbooks influenced by predominant discourses in society? The authors assert that problems and solutions to climate change in textbooks are influenced by dominant discourses of climate change in society. Despite expecting to find a strong emphasis on ecological modernization and a win-win discourse in the Norwegian context, and perhaps a stronger focus on civic environmentalism and global injustice in the South African context, their findings reflected that for both countries, textbooks predominantly leaned towards belief in international agreements and green governmentality. Some emphasis was placed on ecological modernization, particularly in South Africa, while civic environmentalism and global injustice perspectives were marginal and lacked context. The overlapping nature of perspectives identified in the textbooks also demonstrated the complexity of identifying problems and solutions connected to climate change. The authors conclude that political ecology can offer a consistent didactical framework to examine the diversity of interests, perspectives and ‘stories’ about climate change at different scales.
Keywords: C:Norway; C:South Africa; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:geography textbooks; oa:sdg:13 Climate action; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12343 Geography Education and Spatial Thinking; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found